Measurement and analysis of brain deformation during neurosurgery. - Hartkens, T.
Recent studies have shown that the surface of the brain is deformed by up to 20 mm after the skull is opened during neurosurgery, which could lead to substantial error in commercial image-guided surgery systems. We quantitatively analyze the intraoperative brain deformation of 24 subjects to investigate whether simple rules can describe or predict the deformation. Interventional magnetic resonance images acquired at the start and end of the procedure are registered nonrigidly to obtain deformation values throughout the brain. Deformation patterns are investigated quantitatively with respect to the location an magnitude of deformation, and to the distribution and principal direction of the displacements. We also measure the volume change of the lateral ventricles by manual segmentation. Our study indicates that brain shift occurs predominantly in the hemisphere ipsi-lateral to the craniotomy, and that there is more brain deformation during resection procedures than during biopsy or functional procedures. However, the brain deformation patterns are extremely complex in this group of subjects. This paper quantitatively demonstrates that brain deformation occurs not only at the surface, but also in deeper brain structure, and that the principal direction of displacement does not always correspond with the direction of gravity. Therefore, simple computational algorithms that utilize limited intraoperative information (e.g., brain surface shift) will not always accurately predict brain deformation at the lesion.
Keywords: 20 mm; Biopsy; Brain deformation; Brain surface; Brain surface shift; Craniotomy; Deeper brain structure; Deformation patterns; Direction of gravity; Functional procedures; Image-guided surgery systems; Interventional magnetic resonance images; Intraoperative brain deformation; Ipsi-lateral hemisphere; Lateral ventricles; Lesion; Limited intraoperative information; Manual segmentation; Neurosurgery; Nonrigid registration; Principal direction of displacement; Resection procedures; Simple computational algorithms; Simple rules; Skull; Volume change